Health Effects of Fuel Transitions in India: Evidence from Panel Data - Mehtabul Azam (Institute of Labor Economics (IZA), 2023)
We use a nationally representative panel data and combine difference-in-differences methodology with multivalued treatments to look at the impact of cooking fuel switch towards LPG on the probability of short-term adverse respiratory health outcomes such as cough and cough with breathing issues. We find that a switch by households from polluting fuels to LPG reduces the probability of any household member reporting adverse short-term respiratory issues. However, a switch from polluting fuels to a fuel stacking strategy has no impact on the adverse respiratory health issues. A reverse switch by households from LPG to polluting fuels increases the probability of household members reporting adverse health outcomes. Importantly, the clean switch to LPG has a much larger impact for women in reducing the incidence of short-term adverse respiratory outcomes.
Keywords: I1; O12; 330; fuel switching; difference-in-differences; multivalued treatments